(untitled) - Cooper, Gregory John (Cambridge, 2003)
Gregory Cooper's study examines issues in the philosophy of ecology that have been a source of controversy since the existence of ecology as a discipline. These controversies revolve around the concept of a balance of nature; the possibility of general ecological knowledge; and the role of model-building in ecology. The analysis has cross-disciplinary appeal and will interest students and professionals in science, the philosophy of science, and environmental studies as well as policy-makers.
Keywords: Ecology,Sinh thái học; Philosophy,Triết học